Evaluation of the MB/BacT Mycobacterium Detection System for Susceptibility Testing of Mycobacterium tuberculosis - Díaz-Infantes, María S. (American Society for Microbiology, 2000)
The MB/BacT mycobacterium detection system was evaluated for its performance in the susceptibility testing of Mycobacterium tuberculosis. Eighty-three M. tuberculosis isolates were processed. Results for all isoniazid-, rifampin- and streptomycin-susceptible, isoniazid-resistant, and rifampin-resistant M. tuberculosis isolates with the MB/BacT system agreed 100% with those obtained by the agar proportion method. The agreements between the two methods for streptomycin- and ethambutol-resistant isolates were 96.4 and 90.4%, respectively. The susceptibility test results were obtained in 7 days, on average. These data demonstrate that the MB/BacT system is an accurate, nonradiometric method for rapid susceptibility testing of M. tuberculosis.